ANALISIS FAKTOR NIAT PERILAKU KALANGAN MASYARAKAT YANG BERPENGHASILAN TERHADAP PENGGUNAAN E-WALLET - Candy, Candy; Hesniati, Hesniati; Feronika Romadoni, Salsabilah; Sisca, Veni; Novia, Jessica (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
The development of the times has made the technology industry also develop. Currently, there are many people from young people to adults who use financial technology such as OVO, GoPay, LinkAja, ShoppePay, Dana, and so on. The use of this technology is certainly driven by several factors, both internal and external factors. Thus, this study intends to analyze the behavioral intention factor towards the use of e-wallets, especially for people who have income. The method used in this research is a qualitative method by distributing google forms for data collection. Based on the results of data processing using IBM SPSS, it can be concluded that perceived usefulness, brand trust and promotion have a significant positive effect on behavioral intention, while social influence and perceived security have no significant effect.